Technology And the Distribution of The Healthcare Services - Agnieszka BUKOWSKA-PIESTRZYŃSKA; Urszula MOTOWIDLAK (Communications of International Proceedings, 2021)
The delivery of healthcare services that requires the physical meeting of the service provider – the physician, with its recipient – the patient, can now be considered logistically critical (especially under restrictions related to the COVID-19 pandemic). Hence, the establishment of the channels of communication between patients and healthcare entities other than traditional (direct) has become a contemporary challenge. The main thesis of the article is that the employment of modern communication technologies to meet the needs of patients, medical experts and telemedicine service providers increases the diversity of health service distribution channels and as a consequence improves the availability of healthcare system to patients. The article focuses on the essence of service distribution and selected typologies of distribution channels to present the variety of distribution channels available to health services thanks to the selected new technologies. Advantages resulting from such an integration of the distribution channels in healthcare are then indicated.
Keywords: Healthcare; Distribution Channel; Multi-Channel; Telemedicine; E-Health